Pengaruh Supervisi Kepala Sekolah Dan Motivasi Intrinsik Terhadap Kinerja Guru Sd Di Sub Rayon 10 Kecamatan Parung Kabupaten Bogor - Muhamad Yusup; Kidam Kidam (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2019)
This study aims to identify and test the empirical data related to the effect of supervision of the school principal and intrinsic motivation on teacher performance separately or simultaneously. In this study, researchers used a quantitative method with the correlational approach to quantitative data obtained from the object of research is primary teachers sub-rayon 10 Parung-Bogor. Samples were 75 respondents from a total population of 75 elementary school teachers sub-rayon 10 Parung-Bogor. A data collection was done by using a questionnaire / questionnaire. This type of analysis used is the correlation and regression analysis were described descriptively. The results of this study are: First,there is a positive and significant influence between the supervision of the teacher's performance with a correlation coefficient of 0.451 and the determination coefficient R2 of 0.203 Its impact on teacher performance of 20.3% and the remaining 79.7% determined by other factors. The regression coefficient obtained Y = 61 271 + 0,495X1 means that each increase of one unit of organizational commitment scores affect teacher performance improvement score of 0,495 (strong). Second,there is a positive and significant effect between intrinsic motivation on teacher performance with a correlation coefficient of 0.432 and the determination coefficient R2 of 0.187 Its impact on teacher performance of 18.7% and the remaining 81.3% determined by other factors. The regression coefficient obtained Y = 40 359 + 0,635X2 means that each increase of one unit of professional competence score teachers performance improvement score of 0.635. Third,there is a positive and significant influence among supervise principals and intrinsic motivation together on teacher performance with a correlation coefficient of 0.530 and the determination coefficient R2 of 0.281 Its impact on teacher performance of 28.1% and the remaining 71.9% Determined by other factors. The regression coefficient obtained Y = 19 121 + 0,366X1 + 0,446X2 means that each increase of one unit independent scoreof organizational commitment and professional competence simultaneously affect teacher performance improvement score of 0,366+ 0.446 = 0.812.